Photochemical and Photobiological Activity of Zn, Cu, Ni, Co, Fe and Mn Unsubstituted Phthalocyanines - Franklin Vargas; Miguel León; Álvaro Álvarez; Sergio Dasilva; Alexis Maldonado (Chemistry Proceedings)
Phthalocyanines are a group of porphyrin synthetic molecules. These compounds show outstanding photodynamic properties. This is due to their high ability to photogenerate free radicals, such as 1O2 and O.−2. However, the presence of different metals in the central core of phthalocyanines are able to modulate these characteristics. This study demonstrated that the photochemical activity of Zn, Cu, Ni, Co, Fe and Mn unsubstituted phthalocyanines differs, depending on the size and electronic configuration of the central metal. In addition, phthalocyanines showed different levels of photodamage against plasmid pBR322. Outcoming computational calculations will aim to clarify the photodynamic mechanisms of phthalocyanines.